Ситуативно-рольова організація спілкування у навчанні школярів діалогічного мовлення (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2008)
This article vireos cognitive and speech situations, which help junior pupils to obtain conscious and effective dialogical skills.